THE MANAGEMENT FUNCTION OF CONTROLLING BASED ON THE QUR’AN AND HADITH - Khafidhotun Nasikhah (cendekia citra gemilang, 2025)
This literature-based research explains the management function (controlling) from the perspective of the Qur'an and Hadith. If in the parable of a computer device, the Qur'an and Hadith are the software, so that they can become the driving force for the formation of effective educational management controls. Controlling is a function of management, which is defined as supervision, control, and observation. Supervision can be said by observing as well as measuring to find out whether the implementation and work results are in accordance with the plan. In the process, if there are deviations, the main thing in supervision must be observing the causes of the problem as well as looking for solutions. Supervision in the Qur'an and Hadith has the principle of awareness on all parties that in carrying out the mandate, taking policies must be responsible and careful, because it is always under the supervision of Allah SWT. This form of supervision becomes a form of supervision that is not only material but also spiritual. There are several stages that need to be considered in supervision, namely setting standards, measuring performance and correcting deviations